Transscleral Delivery of Dexamethasone-Loaded Microparticles Using a Dissolving Microneedle Array - Rawan Fitaihi; Shorooq Abukhamees; Mine Orlu; Duncan Q. M. Craig (MDPI AG, 2023)
Microneedles (MNs) have attracted considerable interest as a means of ocular drug delivery, a challenging delivery route due to the limitations imposed by the various biological barriers associated with this organ. In this study, a novel ocular drug delivery system was developed by formulating a dissolvable MN array containing dexamethasone-loaded PLGA microparticles for scleral drug deposition. The microparticles serve as a drug reservoir for controlled transscleral delivery. The MNs displayed sufficient mechanical strength to penetrate the porcine sclera. Dexamethasone (Dex) scleral permeation was significantly higher than in topically instilled dosage forms. The MN system was able to distribute the drug through the ocular globe, with 19.2% of the administered Dex detected in the vitreous humour. Additionally, images of the sectioned sclera confirmed the diffusion of fluorescent-labelled microparticles within the scleral matrix. The system therefore represents a potential approach for minimally invasive Dex delivery to the posterior of the eye, which lends itself to self-administration and hence high patient convenience.